Răspuns :
1)... a). x-2 = x√3-2√3 ⇒ x - x√3 = 2-2√3 ⇔ x(1-√3) = 2(1-√3) ⇒ x = 2 ∈ Ox ;
b). pt x=2 ... f(2) = 0 ⇒ A(2;0) ∈ G(f(x))
x=0 ... f(0) = -2 ⇒ B(0;-2) ∈ G(f(x))
deci f(x) trece prin punctele A si B !
pt. x=0 ... g(0)= - 2√3 adica C(0;-2√3)
x=2 ... g(2)= +2√3 adica D(2; 2√3)
deci g(x) trece prin punctele C si D !
2)... a). ⇒ 1,5x+1 = 2x+0,5 ⇒ 1-0,5=2x-1,5x ⇔ 0,5x = 0,5 deci x=1
si g(1) = 2+1,5 =3,5 .............. deci y=3,5
⇒ [tex]f(x)\cap{g(x)}=P(1\;;\;3,5)[/tex]
b). pt x=2 ... f(2) = 0 ⇒ A(2;0) ∈ G(f(x))
x=0 ... f(0) = -2 ⇒ B(0;-2) ∈ G(f(x))
deci f(x) trece prin punctele A si B !
pt. x=0 ... g(0)= - 2√3 adica C(0;-2√3)
x=2 ... g(2)= +2√3 adica D(2; 2√3)
deci g(x) trece prin punctele C si D !
2)... a). ⇒ 1,5x+1 = 2x+0,5 ⇒ 1-0,5=2x-1,5x ⇔ 0,5x = 0,5 deci x=1
si g(1) = 2+1,5 =3,5 .............. deci y=3,5
⇒ [tex]f(x)\cap{g(x)}=P(1\;;\;3,5)[/tex]